2004
DOI: 10.1111/j.1365-2958.2004.04339.x
|View full text |Cite
|
Sign up to set email alerts
|

An alternative pathway for reduced folate biosynthesis in bacteria and halophilic archaea

Abstract: Whereas tetrahydrofolate is an essential cofactor in all bacteria, the gene that encodes the enzyme dihydrofolate reductase (DHFR) could not be identified in many of the bacteria whose genomes have been entirely sequenced. In this communication we show that the halophilic archaea Halobacterium salinarum and Haloarcula marismortui contain genes coding for proteins with an N-terminal domain homologous to dihydrofolate synthase (FolC) and a C-terminal domain homologous to dihydropteroate synthase (FolP). These ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 28 publications
2
40
0
Order By: Relevance
“…Alternatively, the intracellular concentration of dihydrofolate might reach a level at which enzymes with low DHFR reductase activity and insensitivity to TMP are sufficiently active to recycle the dihydrofolate pool and to sustain bacterial growth. Indeed, it has been shown that short-chain dehydrogenases, such as FolM in E. coli (11) or the dihydropteroate synthase from Helicobacter pylori, have TMP-independent DHFR activity (22). In agreement with this model, strain CCH290 is only weakly resistant to the combination of both antibiotics (SXT) ( Table 3), SU decreasing the synthesis of dihydrofolate and rendering the strain sensitive to TMP.…”
Section: Discussionsupporting
confidence: 66%
“…Alternatively, the intracellular concentration of dihydrofolate might reach a level at which enzymes with low DHFR reductase activity and insensitivity to TMP are sufficiently active to recycle the dihydrofolate pool and to sustain bacterial growth. Indeed, it has been shown that short-chain dehydrogenases, such as FolM in E. coli (11) or the dihydropteroate synthase from Helicobacter pylori, have TMP-independent DHFR activity (22). In agreement with this model, strain CCH290 is only weakly resistant to the combination of both antibiotics (SXT) ( Table 3), SU decreasing the synthesis of dihydrofolate and rendering the strain sensitive to TMP.…”
Section: Discussionsupporting
confidence: 66%
“…As in H. volcanii, tetrahydrofolate derivatives are essential methyl donors for several metabolic reactions, the predicted phenotype for HVO_2348 deletion strains (VDC3234, VDC 3235 and VDC 3236) is the requirement for dT, hypoxanthine and pantothenate on Hv-CA (minimal medium supplemented with casaminoacids (Levin et al 2004)). As predicted, the mutant strains were auxotrophic for dT ( Figure 5).…”
Section: A Gateway Platform For Gene Deletion In H Volcaniimentioning
confidence: 99%
“…A very interesting additional application of designed mutants with an inactivated essential function has been reported recently. They can be used to identify novel non-homologous proteins from other species that are able to complement the missing reaction, and that were hitherto annotated as hypothetical proteins (Levin et al, 2004).…”
Section: Genetics and Functional Genomicsmentioning
confidence: 99%